ANALISIS FAKTOR JUMLAH BAYI LAHIR HIDUP DI SUMATERA BARAT - Arifman Fajri; Syamsul Amar; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study intends to determine effect of income level, education level of married woman, married woman labor force participation, total health budget, and number of medical personnel on fertility in districts / cities in West Sumatra. This study uses data from the BPS and the West Sumatra Health Office in 2012-2017. The analysis technique used is Panel Data Regression Analysis. The results showed that (1) The level of income did not have a significant negative effect on the number of live births in the West Sumatra (2) The level education of married woman had a significantly positive effect on the number of live births in West Sumatra; (3) Labor force participation of married woman has a significant effect on the number of live births in West Sumatra; (4) The amount of the health budget has a significant positive effect on the number of live births in West Sumatra; (5) The number of medical personnel has a significant positive effect on the number of live births in West Sumatra; (6) Income level, education level of married woman, labor force participation of married woman, number of health budgets, and the number of medical personnel simultaneously have a significant effect on the number of live births in West Sumatra.